EXAMINING PERSPECTIVE ON PAYMENT ECOSYSTEM SERVICES: A CASE STUDY OF MELAKA AMONG GENERATION Z - Amri , Anis Maisarah Yang; Ayub , Alysha Wafiyyah; Krishnan, Devika; Hassan, Suziana (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2026)
Payment for Ecosystem Services (PES) is a market-based environmental policy instrument that provides financial incentives to individuals or organizations for managing land and natural resources in ways that generate ecological benefits, such as water purification, biodiversity conservation, and carbon sequestration. Despite the increasing implementation of PES initiatives worldwide, limited empirical studies have examined how younger generations, particularly Generation Z, perceive and respond to such environmental policy mechanisms. Therefore, this study aims to examine the affective, cognitive, and behavioural attributes of Generation Z toward Payment for Ecosystem Services initiatives. A quantitative research design was employed using a structured survey instrument adapted from previously validated studies to ensure reliability and measurement accuracy. Data were collected from Generation Z respondents in Melaka and analysed using statistical techniques to assess the relationships between affective, cognitive, and behavioural dimensions and overall perceptions of PES. The findings indicate that Generation Z demonstrates varying levels of awareness and attitudes toward PES, with affective and cognitive attributes significantly influencing their behavioural intentions to support ecosystem conservation initiatives. These results contribute to the understanding of youth perspectives on environmental economic instruments and provide insights for policymakers in designing more effective PES awareness and engagement strategies.